The Term Structure of Interest Rates - Culbertson, J. M. (Quarterly Journal of Economics, 1957)
I. The elements of term structure theory, 489. — II. The role of debt liquidity differences in the rate structure, 491. — III. The role of speculative activity in the term structure, 496. — IV. Changes in the maturity structure of demand for funds, 502. — V. Yields on short-term and long-term U. S. government securities 1920–1957, 504. — VI. Some implications for credit policy, 516.